On the Ecology of Faith - Sztumski, Wiesław (Studia Ecologiae et Bioethicae, 2020)
Nowadays, we observe a progressive depreciation of faith together will the degradation of the social environment. It concerns faith in a broad sense here, not only religious but also faith in ideals, in ourselves, and the confidence to other people and to different social institutions. We should not permit the further deflation of faith regarding the role which it plays in the life of people, their thinking, and doing, in integrating them in a world community as a result of globalization. On the contrary, it is necessary to strengthen our faith to care for it. Therefore, it is necessary to create an ecology of faith and to develop large, deep, and many-sided study in this domain, because faith is a means for survival in the present endangered life environment.